Trans-Atlantic Sheep, Regional Development, and the Cape Breton Development Corporation, 1972-1982 - Langford, Will (Acadiensis, 2017)
Cape Breton Development Corporation (DEVCO) – a federal Crown corporation created in 1967 – was charged with stimulating employment to compensate for the decline of island coal mining. Following the failure of industrial promotion, DEVCO adopted a participatory regional development practice between 1972 and 1982. With specific reference to sheep producers, this article argues that DEVCO focused on imparting entrepreneurship, boosting production, and selling a particular kind of Cape Breton. However, DEVCO objectives were undermined by the very capitalist processes they sought to amend. The Cape Breton sheep story provides a way into the broader history of regional development in these years.